Seroprevalence of Helicobacter pylori infection in adolescents and adults in Babol - M Zamani (Majallah-i Dānishgāh-i ̒Ulūm-i Pizishkī-i Bābul, 2017)
-BACKGROUND AND OBJECTIVE: Helicobacter pylori is an important causative factor for chronic gastritis, peptic ulcer and gastric cancer. Based on the reports, about half of the world population are infected with this bacterium. The present study was designed with the purpose of investigation of H. pylori infection rate in adolescents and adults of Amirkola in Babol METHODS: This cross-sectional study was performed on individuals who referred to the health and treatment center of Amirkola, Babol, for the premarital counseling during December 2015 and January 2016. The blood sample of subjects was assessed for H. pylori status using enzyme-linked immunosorbent assay. The demographic data were collected. FINDINGS: Of 207 participants, 100 (48.3%) were male and others were female. The mean age was 25.35±5.82 (14-46) years. Rate of H. pylori was 43%, seen more frequently in the age group 21-25 years (37.2%). The infection rate was 49% and 37.4% in males and females, respectively, but the difference was not significant. The age group more than 30 was associated with increased risk of infection (odds ratio [OR]=5.25, 95% confidence interval [CI]: 1.86-14.78). There was also a significant correlation between the infection and level of education (p=0.041) and higher diploma was inversely associated with the infection (OR=0.4, 95% CI: 0.18-0.91). No significant relation was found between the infection and blood groups and residency. CONCLUSION: The results of study indicated a considerable rate of H. pylori infection in adolescents and adults of Amirkola. Also, it was determined that higher education can have a protective role against H. pylori infection